Global scientific production on LADM-based research: A bibliometric analysis from 2012 to 2020 - Polat, Zeynel Abidin; Alkan, Mehmet; Paulsson, Jenny; Paasch, Jesper M.; Kalogianni, Eftychia (ELSEVIER SCI LTD, 2022)
Multiple Land Administration Domain Model (LADM) related studies have been carried out in two decades. ISO 19152 LADM is an international standard and an abstract, conceptual model covering the land administration domain (including those over land and water and elements above and below the earth's surface). The LADM is considered an important component for managing and developing land administration systems worldwide. In the context of this study's, scientific publications related to LADM are examined to carry out a bibliometric analysis on LADM research from 2012 to 2020. The extent of this investigation is limited to the Scopus database for scientific publications. All databases belong to the most extensive peer-reviewed summary and citation databases. It is noted that this study is based on the same principles as the research published by Paulsson and Paasch (2015), building on existing knowledge and aiming to add value in support to the current development of Edition II of the LADM. In this study, which covers 2012-2020, 175 LADM related scientific publications were found in the Scopus database. When the distribution of publications in journals is examined, Land Use Policy has the most published manuscripts related to ISO 19152 LADM. This analysis considers author identification, type of paper, organisational issues, and bibliometric analysis components. The analysis considered articles, books, and proceedings directly related to the LADM and included in the Scopus database or conference and workshop proceedings. For this, articles and books were selected from the Scopus database. Also, the proceedings were selected from those presented in the International Federation of Surveyors (FIG) events and workshops on LADM. Overall, this paper aims to arrange and present the global scientific production on LADM-based research.
Keywords: ISO 19152; LADM; Bibliometric Analysis; Scopus database; FIG; ADMINISTRATION DOMAIN MODEL; TRENDS; INFORMATION; EVOLUTION; Environmental Sciences & Ecology